2019
DOI: 10.3126/jist.v24i1.24626
|View full text |Cite
|
Sign up to set email alerts
|

Assemblage of Insects on Medicinal Plants: An Insight from ICIMOD Herbal Garden in Godavari of Lalitpur, Nepal

Abstract: Present study was conducted within the herbal garden of International Centre for Integrated Mountain Development (ICIMOD) in Godawari of Kathmandu valley to explore the insect communities in medicinal plants. Five medicinal plants, viz. Rauvolfia serpentina (= Sarpagandha), Urtica dioca (= Sissnu), Zanthoxylum armatum (= Timur), Valeriana jatamansii (= Sungandhawal) and Mentha spicata (= Pudina) were selected for the study. Insects were randomly sampled during four seasons from September 2017 to June 2018 usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Specimens from traps were rst separated from debris. Each specimen was identi ed through suitable identi cation keys, morphological characters, citizen identi cation, and digital application (Perry et al, 2021;Bhusal et al, 2019). The current study used the automated insect identi cation technology of iOS (the iPhone Operating System).…”
Section: Insect Identi Cationmentioning
confidence: 99%
“…Specimens from traps were rst separated from debris. Each specimen was identi ed through suitable identi cation keys, morphological characters, citizen identi cation, and digital application (Perry et al, 2021;Bhusal et al, 2019). The current study used the automated insect identi cation technology of iOS (the iPhone Operating System).…”
Section: Insect Identi Cationmentioning
confidence: 99%
“…The use of foliar and systemic insecticides such as imidacloprid, fenpropathrin, chlorpyrifos and dimethoate are considered an effective approach to reduce the citrus psyllid numbers. The approach of using the aqueous solution of either 0.05% dimethoate or 0.02% chlorpyrifos or imidacloprid at bud burst stage for the control of citrus psyllid is also followed in India and China (Department of Agriculture, 2011) and are also readily available in the Nepalese markets (Bhusal et al, 2019;Diwakar et al, 2008). It is found that systemic soil applied imidacloprid properties has less impact on natural enemies (Boina et al, 2009) and also provides a longer period of protection than many foliar insecticides (Grafton-Cardwell et al, 2013) The systemic soil applied imidacloprid were also found to decrease their potential of acquiring and transmitting the HLB pathogen (Boina et al, 2009).…”
Section: Chemical Managementmentioning
confidence: 99%
“…In some studies, essential oil from Artemisia absinthium is also found toxic to the psyllids but its toxicity was reported to be weaker than synthetic insecticides (Rizvi et al, 2018). However, the availability of the essential oils in the Nepalese market might render its use in HLB management (Bhusal et al, 2019).…”
Section: Chemical Managementmentioning
confidence: 99%